Surgical options in experimental porcine model for endovascular training in complex vascular lesions. Issue 3 (June 2019) - Arikan, Fuat; Gandara, Dario; Esteves, Marielle; Tomasello, Alejandro; Sahuquillo, Juan
We describe a new, elegant, two-phase, microsurgical method that minimizes the surgical preparation time for different complex vascular lesions in a swine model. In the first phase, the model is prepared microsurgically in the experimental laboratory using arterial or/and venous grafts. In the second phase, the model is implanted in the experimental animal. This two-fold method allows for increasing the complexity and accuracy of the model while reducing preparation time on the day of the training session.